Towards Library 2.0: The Adoption of Web 2.0 Applications in Academic Library Websites in Malaysia - Awang, Nor Hazidah (2012)
The functions of today’s libraries have evolved concurrent to the advancement of computer technology in general. To keep abreast with the trends, academic libraries have also started to adopt Web 2.0 in widening their service capacity. Academic libraries currently have put a lot of efforts to construct a more interactive and lively services in assisting students to gain the most out of their learning experience. Hence, this paper examines Web 2.0 applications by academic library websites in Malaysia in their effort to promote outstanding services, particularly in supporting research activities and responses to users’ comments. A number of academic libraries in Malaysia were selected for the purpose of the investigation and the results should provide some useful insights in expanding the avenues of library services.